Artificial Intelligence for Educ-AI-tion: AI Integration on Scientific Writing Strategies in Lecturer Training Programs - Ismail Ismail; Umiyati Jabri (Universitas Muhammadiyah Enrekang, 2024)
The use of artificial intelligence (AI) in the context of education has become an increasingly relevant topic in the modern era. This study aims to explore the integration of AI into lecturer training programs at Universitas Muhammadiyah Enrekang, focusing on the development of effective scientific writing strategies. A qualitative approach with a case study design is employed in this research, involving interviews with lecturers and training instructors, observation during training sessions, and analysis of relevant training program documents. The findings highlight the need for AI integration in the development of scientific writing skills, as well as various strategies that can be implemented in training programs. Challenges and opportunities related to this integration are also identified. This study contributes to understanding the importance of AI usage in education and the professional development of lecturers, particularly at Universitas Muhammadiyah Enrekang.